ABU NASR FARABI’S VIEWS ON NATIONAL IDENTITY AND INTERCULTURAL DIALOGUE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the views of the great thinker Abu Nasr al-Farabi on national identity and intercultural dialogue. It highlights the significance of his ideas on human beings, society, and culture in the context of modern globalization. Furthermore, the role of Farabi’s teachings in fostering dialogue between Eastern and Western civilizations is substantiated from a scientific perspective.